Preparation of Aligned Steel Fiber Reinforced Cementitious Composite and Its Flexural Behavior - Mu, Ru (J Vis Exp, 2018)
The aim of this work is to present an approach, inspired by the way in which a compass needle maintains a consistent orientation under the action of the Earth's magnetic field, for manufacturing a cementitious composite reinforced with aligned steel fibers. Aligned steel fiber reinforced cementitious composites (ASFRC) were prepared by applying a uniform electromagnetic field to fresh mortar containing short steel fibers, whereby the short steel fibers were driven to rotate in alignment with the magnetic field. The degree of alignment of steel fibers in hardened ASFRC was assessed both by counting steel fibers in fractured cross-sections and by X-ray computed tomography analysis. The results from the two methods show that the steel fibers in ASFRC were highly aligned while the steel fibers in non-magnetically treated composites were randomly distributed. The aligned steel fibers had a much higher reinforcing efficiency, and the composites, therefore, exhibited significantly enhanced flexural strength and toughness. The ASFRC is thus superior to SFRC in that it can withstand greater tensile stress and more effectively resist cracking.